Health Hazards and Health Seeking Behaviors among Tannery Workers Residing at Tannery Industrial Area (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2026)
Background: The leather industry and its products have a substantial impact on the economy of Bangladesh and have been recognized as a highly significant sector. Nevertheless, tannery poses potential risks to workers due to exposure to harmful chemicals and pollutants linked with tannery activities. The objective of this study was to evaluate the health hazards and healthcare-seeking behavior experienced by tannery workers residing in close proximity to the tannery area. Materials and methods: This cross-sectional study was carried out among tannery workers residing in the vicinity of the tannery industrial area in Hemayetpur, Savar, Dhaka. A total of 402 participants were conveniently interviewed in person using a pre-tested semi-structured questionnaire from January to December 2023. Results: The majority of participants were male (88%) predominantly young adults aged 20-30. In terms of employment, 34.6% worked in machinery-related tasks, with 66.4% having done so for 3-8 years. Self-reported health issues included joint pain (49.0%), frequent fever (33.3%), allergies (43.0%), chronic headaches (35.8%), itching (35.8%), rashes (19.9%), and coughing (35.8%). Statistically significant associations were found between these health problems and the duration of stay, department of work, and gender (p